Effects of foliar applied copper and boron on fungal diseases and rice yield on cultivar MR219 - Liew, Yew Ann; Syed Rastan, Syed Omar; Mohd Hanif, Ahmad Husni; Mior Ahmad, Zainal Abidin; Abdullah, Nur Ashikin Psyquay (Universiti Putra Malaysia Press, 2012)
Long-term intensive cropping on the same piece of land with high-yielding varieties often exhausts the availability of soil micronutrients. Poor management of plant micronutrients has become a hurdle in the effort to increase rice production in Malaysia. The new rice variety, MR 219, was introduced to bring the yield potential up to 10 t ha-1. However, to sustain the high yield, more N-fertilizer input is needed and this will increase incidences of disease. Moreover, nutrients imbalance due to limited micronutrients application may worsen the situation. In this study, two seasons of field experiments were conducted at Sawah Sempadan, Kampung Seri Tiram Jaya, Tanjong Karang (3Â° 28â€™ 0â€ North, 101Â° 13â€™ 0â€ East) in the off season of 2007 (July 2007 â€“ November 2007) and the main season of 2008 (January 2008 â€“ May 2008), using high yielding cultivar of MR219 to evaluate the effects of copper (Cu) and boron (B) foliar applications on the reduction of fungal diseases, and also to evaluate the effects of foliar Cu and B applications on rice production. Nine combinations of Cu and B treatment at varying levels of Cu (0 â€“ 20 ppm) and B (0 â€“ 20 ppm) were replicated 4 times and applied through foliar spray at three different times, namely, 30, 45 and 60 days after seeding (DAS). The foliar application of Cu and B was found to be able to reduce fungal disease infestation in MR219 rice cultivar and subsequently increase rice yield. Meanwhile, the foliar treatment of Cu and B applied in combination at level T7 (7.53 t ha-1), T9 (7.33 t ha-1), T8 (7.28 t ha-1) and T6 (7.06 t ha-1) produced significantly higher (P >0.05) rice yield as compared with the control, T1 (5.75 t ha-1). A significant reduction in disease scoring was also recorded in the experiment where foliar treatment at level T9 (20 ppm Cu + 20 ppm B) cut down 5% of the disease incidence in MR219 rice plant. Rice yield components such as productive tiller m-2, number of spikelets panicle-1, percentage of filled grains and 1,000-grain weight have also shown remarkable increments as a result of the Cu and B foliar treatment.